2021
DOI: 10.1038/s41420-020-00395-8
|View full text |Cite
|
Sign up to set email alerts
|

GDF15 promotes glioma stem cell-like phenotype via regulation of ERK1/2–c-Fos–LIF signaling

Abstract: Growth differentiation factor 15 (GDF15), a member of the transforming growth factor β family, is associated with tumor progression, metastasis, and cell apoptosis. However, controversy persists regarding the role of GDF15 in different tumor types, and its function in glioma stem cells (GSCs) remains unknown. Here, we report that GDF15 promotes the GSC-like phenotype in GSC-like cells (GSCLCs) through the activation of leukemia inhibitor factor (LIF)–STAT3 signaling. Mechanistically, GDF15 was found to upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…To investigate the cell source of the two cytokines, we checked literature and analyzed data of the single cell sequencing on GBM by Wang et al 41 . CCL2 was found expressed by GBM cells and macrophages 34 - 37 , but LIF mainly expressed in GBM cells 38 - 40 , which were also supported by single cell sequencing data ( Figure S5 B) . Through immunofluorescence, we found that LIF rarely expressed in macrophages labelled with CD68 ( Figure S5 C) , but highly expressed in GBM cells labelled with Olig2 (Figure 5 B) .…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…To investigate the cell source of the two cytokines, we checked literature and analyzed data of the single cell sequencing on GBM by Wang et al 41 . CCL2 was found expressed by GBM cells and macrophages 34 - 37 , but LIF mainly expressed in GBM cells 38 - 40 , which were also supported by single cell sequencing data ( Figure S5 B) . Through immunofluorescence, we found that LIF rarely expressed in macrophages labelled with CD68 ( Figure S5 C) , but highly expressed in GBM cells labelled with Olig2 (Figure 5 B) .…”
Section: Resultssupporting
confidence: 77%
“…IHC result further confirmed high expression of LIF and CCL2 in mGBM1_C compared to mGBM1_A and B (Figure 5 A) . Since CCL2 plays strong chemotaxis function to recruit macrophage and LIF activates STAT3 pathway 34 - 40 , we performed IHC to examine macrophage infiltration using CD86 antibody and activation of STAT3 using p-STAT3 antibody. The data indicated the consistence between CCL2 and CD68, as well as, LIF and p-STAT3 (Figure 5 A) .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, p53 can regulate maternal reproduction by binding to the intron, located in +873/+898 [ 26 ]. The detailed gene structure of LIF is shown in Figure 1 [ 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Lif and Lif Receptormentioning
confidence: 99%
“…Apoptosis is a process in which cell death occurs in an orderly manner and is crucial for the maintenance of internal homeostasis ( 64 ). Owing to its reported function as a stress-response protein, GDF15 has been reported to regulate apoptosis ( 65 ). GDF15 is a downstream target of methylseleninic acid (MSA), where GDF15 knockdown significantly inhibited the apoptosis of prostate cancer cells mediated by MSA ( 66 , 67 ).…”
Section: Biological Functions Of Gdf15mentioning
confidence: 99%